La recreación literaria de la historia: Escipión el Africano de Ross Leckie - Montero Cartelle, Enrique (Cuadernos de Filología Clásica. Estudios Latinos, 2005)
The object of this study is to analyse the literary tecnique used by Ross Leckie to compose the historical novel Scipio, focusing this analysis on the relation between history and literary fiction.